1991
DOI: 10.1093/infdis/163.4.825
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Model of Early Central Nervous System Syphilis

Abstract: Although up to 40% of patients with early syphilis have evidence of central nervous system (CNS) invasion by Treponema pallidum, the pathogenesis of CNS syphilis is not understood. A rabbit model that mimics early CNS involvement in humans was developed and characterized. Mild cerebrospinal fluid pleocytosis was evident 2 weeks after intracisternal inoculation of T. pallidum and peaked at 9 weeks. The VDRL test in cerebrospinal fluid was reactive in 24% of animals, most commonly at 9 weeks after infection. T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…Both neurosyphilis and Lyme neuroborreliosis are characterized by an early invasion of the nervous system, as shown by experimental evidence in animal models [10], [16]. This is consistent with the finding of a clinically silent CSF pleocytosis in many patients at an early stage of infection, likely representing early nervous system invasion.…”
Section: The Borreliosessupporting
confidence: 83%
See 1 more Smart Citation
“…Both neurosyphilis and Lyme neuroborreliosis are characterized by an early invasion of the nervous system, as shown by experimental evidence in animal models [10], [16]. This is consistent with the finding of a clinically silent CSF pleocytosis in many patients at an early stage of infection, likely representing early nervous system invasion.…”
Section: The Borreliosessupporting
confidence: 83%
“…Likewise, uveitis has been reported in rabbits inoculated via the intradermal route [9]. Meningeal and ocular manifestations in this model recreate the early neurosyphilis in patients [10]. NHP were infected by the intrathecal route resulting in objective neurosyphilis findings that included pleocytosis in the CSF, persistence of organisms for several weeks, and changes in cytokine profiles.…”
Section: Syphilismentioning
confidence: 58%
“…After testicular infection of rabbits, treponemes were visible in the lymph nodes, brain, and aqueous humor, and in the CSF as early as 18 h postinoculation (73). T. pallidum RNA has also been detected by reverse transcription-PCR in the CSF of intravenously infected animals (306), and Marra et al found that 6% of rabbits inoculated by the intrathecal method developed ocular syphilis (192), demonstrating that organisms are able to travel from the CSF to the eye. Not only do treponemes disseminate to distant sites but they also can persist in distant tissues during chronic infection.…”
Section: Invasionmentioning
confidence: 99%
“…Serologic analysis and CSF RT-PCR. Serum VDRL and fluorescent treponemal antibody-absorbed (FTA-ABS) tests were performed as described elsewhere [12]. CSF-VDRL was performed using standard methods [13].…”
Section: Animalsmentioning
confidence: 99%